Effect of Preannealing on Microstructural Evolution and Tensile Properties of a Novel Nickel‐Based Superalloy. Issue 6 (17th April 2020) - Lv, Shaomin; Jia, Chonglin; He, Xinbo; Wan, Zhipeng; Chen, Zheng; Qu, Xuanhui
Abstract : The effect of preannealing (PA) on microstructural evolution and tensile properties of a novel nickel‐based alloy GH4065 is investigated. Particularly, the study of PA in disc superalloys is reported herein for the first time. The detailed strengthening mechanisms of specimens under different heat treatment cycles are identified by electron backscatter diffraction (EBSD) and transmission electron microscope (TEM) observations. The results reveal that the PA treatment after deformation improves the homogeneity of the microstructure due to static recrystallization (SRX). Multimodal size distributions and the morphology of γ′ precipitates are found after the PA + solution + aging (PASA). Also, the distributions of secondary and tertiary γ′ precipitates are optimized due to the PA. The tensile strength of GH4065 alloy after PASA is higher than that of as‐forged (AF) alloy and solution + aging (SA) alloy attributed to the improved microstructure during PA treatment. Compared with the SA specimens, the specimens of GH4065 alloy after PASA treatment lead to significant strengthening as the yield strength increased to more than 150 MPa, which is mainly due to the contribution from annealing twins and microtwins strengthening, as well as the grain refinement and γ′ precipitation strengthening. Abstract : The preannealing + solution + aging (PASA) treatment is proposed for a novel nickel‐based alloy GH4065. The results indicate that the PASA treatment promotes the occurrence of static recrystallization (SRX) and the generation of γ′ precipitates characterized by multimodal size distributions and morphology.